Shariapreneur Interest : Analysis Of Sharia Business Knowledge and Motivation (Studies On Students Of The Islamic Economics Study Program Bandung City Universities - Ibadurrohman Siddiq; Juliana Juliana; Fitranty Adirestuty (Review of Islamic Economics and Finance (RIEF), 2020)
One of the requirements for a country to change its status to a developed country is the number of entrepreneurs who reach 2% of the total population in productive age. However, currently, the total entrepreneurship in Indonesia is still at 0.7% of the total productive age population. As the largest Muslim country globally, there is only 0.18% of Indonesian Muslim entrepreneurs. The purpose of this study was to determine the high interest of students to become shariapreneurs. The research method used is the descriptive method with a quantitative approach. The population in this study were students of the Islamic economics study program at the State University of Bandung. The samples taken in this study were 251 people. The data analysis technique used is Multiple Linear Regression. Furthermore, in the results of this study, Islamic business knowledge has a positive and significant effect on shariapreneur interest and motivation, which has positive and significant results on shariapreneur interest. Researchers hope that the results of this study can provide benefits to various parties in increasing the interest of shariapreneurs in Islamic economics study program students in the State University of Bandung City.